Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines. Issue 6 (June 2014) - Luque, P. L.; Rodriguez‐Marin, E.; Landa, J.; Ruiz, M.; Quelle, P.; Macias, D.; Ortiz De Urbina, J. M.
<x xml:space="preserve">Abstract</x> This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus. Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data (L∞ = 327·4; k = 0·097; t0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.